Effect of compost and slow-release fertilizers addition on soil biochemistry and yield of maize (Zea mays L.) in Oaxaca, Mexico - Bautista-Cruz, Angélica (2014)
The effect of Bokashi (B, a fermented compost), slow-release fertilizers (SRFs) and their combined application on mycorrhizal colonization (MC), soil invertase, cellulase, acid (AcP) and alkaline (AlP) phosphatases activities and maize (Zea mays L.) yield was investigated in terrace (TS) and valley (VS) soils in Oaxaca, Mexico. A complete randomized design, seven fertilizer treatments and four replications were used: unamended control (C); conventional fertilization (90-46-00 NPK) (CF); B; SRF1 (Multigro 6®, 21-14-10 NPK); SRF2 (Multigro 3®, 24-05-14 NPK); B+SRF1; B+SRF2. Highest root colonization percentage: CF in VS, and SRF2 in TS. Highest extraradical mycelium length: B, B+SRF1, CF in VS, and B+SRF1 in TS. In both soils, B increased the spore number. Highest AcP activity: B, SRF2 in VS, and B+SRF1, B+SRF2 in TS. Highest AlP activity: B+SRF1, CF in VS, and C in TS. Highest invertase activity: B+SRF1, SRF2, CF in VS, and B in TS. Grain yield only increased with B in VS. The significant interaction soil type × fertilizer treatment for the majority of the biological soil properties analyzed suggests that MC and soil enzyme activity response to fertilization was influenced by soil type. Bokashi, alone or combined with SRFs improves biological soil fertility in maize fields.